استخدام الحاسوب في الأعمال الإدارية في جامعة تشرين (دراسة ميدانية) - الرفاعي, عبد الهادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن التطورات المتسارعة في المجالات التقنية ولا سيما في مجال الحاسوب والبرمجيات أسهمت وما تزال تسهم في تبسيط العمليات الإدارية وتداول المعلومات وسرعة انتقالها. فقد تناولنا من خلال هذه الدراسة المبسطة قضية استخدام الحاسوب في الأعمال الإدارية في الكليات والمديريات المركزية في جامعة تشرين, وذلك من خلال الدراسة الميدانية التي قمنا بإجرائها, والتي استطعنا من خلالها التوصل إلى بعض النتائج واقتراح بعض التوصيات التي تسهم في تطوير أداء الأعمال, ومن أهم هذه النتائج: إن استخدام الحاسوب لا يؤدي بالضرورة في بعض المديريات إلى الاستغناء عن الورقيات, كما أن إنشاء شبكة حواسيب محلية مع قاعدة بيانات في وزارة التعليم العالي غير قابل للتطبيق بشكل كامل في بعض المديريات, مثل شعب الامتحانات، نظراً لطبيعة المعلومات في هذه المديريات. The pace of technological developments, especially the hardware and software have contributed to facilitating the administrative procedures, accessing information and transferring it. This study has focused on using computer to conduct administrative procedures in both faculties and central administration of Tishreen University. There have been some important conclusions which could help to form some suggestions concerning the process of developing the work performance. Of these results, it has been found that the use of computer will not eliminate the paper works in some directorates. Moreover, the setting of local network alongside database of the Ministry of Higher Education at some directorates is unnecessary. For example, at the Examination Segments due to the nature of the information in these directorates.